Remote Sensing Observations of Ocean Surface Chlorophyll and Temperature with the Impact of Cyclones and Depressions over the Bay of Bengal Water. Issue 1 (2nd January 2016) - Sarangi, R. K.
ABSTRACT: MODIS-Aqua derived eight-day composite chlorophyll concentration data analyzed to study the impact of cyclones and depressions on the Bay of Bengal productivity. A total of 15 cyclonic storms and depressions picked up from the India Meteorological Department datasets. MODIS-Aqua data analyzed during October 2002 to December 2009. There was observation of depressions (D), deep depressions (DD), cyclonic storms (CS), severe cyclonic storms (SCS), and very severe cyclonic storms (VSCS) with categories of intensities ("T" numbers 1.5–6) and wind speeds (25–108 knots). The chlorophyll concentration observed to be high (1.0–5.0 mg/m 3 ) with the impact in the coastal and offshore waters. Quickscat scatterometer data showed high wind speed (about 10 meters/second). Sea surface temperature (SST) observed to be decreased (roughly 2°C) with effect of cyclones. The cyclone numbers, intensity, and chlorophyll concentration has been observed to be increasing from 2002 to 2009, with observation of VSCS "Sidr" during 2007. The study would be interesting to link carbon flux/sequestration, marine food chain, and harnessing fishery resources in a postcyclone period.